Farmān-e-Shāḥī’s Role in Islamic Legislation During Mughal Rule - Mamoona Yasmeen; Abu Bakar Buttah (Pakistan Journal of Islamic Research)
This research intends to focus on the role of Fārmān-e-Shāḥī issued by the Mughal rulers from Bābar to Aurangẓaib in Islamic legislation. Not only had Fārmān-e-Shāḥī played a robust constitutional role, but also executed its role in legislating and implementing civil as well as Islamic criminal and procedural codes. Tracing the evolutionary process of the legislation of Fārmān-e-Shāḥī, the article finds the Farmāns instrumental in legislating Islamic jurisprudence and codification. In fact, pre-Mughal evolution of Islamic law into a criminal and procedural code had its own significance and legal value for the religious backing during the Mughal period. Hence, Fārmān-e-Shāḥī has become instrumental for innovation and codification vis-a-viz Islamic injunctions already codified. The existing study reviews the legislation regarding Islamic laws and Farmāns’ role in the Islamic legislation during Mughal India, their bearings on further legislation and the progression of state legislation regarding Islamic laws. It also highlights the role it has in the evolution of Islamic jurisprudence in British India as well as regional states in India.